Diffusion-Tensor Imaging of Uterine Cervical Carcinoma: Correlation With Histopathologic Findings. Issue 3 (May 2020) - Yamada, Ichiro; Oshima, Noriko; Wakabayashi, Akira; Miyasaka, Naoyuki; Wakana, Kimio; Saida, Yukihisa; Tateishi, Ukihide; Kobayashi, Daisuke
Abstract : Abstract: The authors investigated the usefulness of diffusion-tensor imaging (DTI) for evaluating tumor invasion depth, histologic grade, and lymph node metastasis in patients with cervical carcinoma (CC). Fifteen consecutive patients with histologically confirmed CC underwent 1.5-T magnetic resonance imaging and DTI. The CCs were clearly depicted as hypointense areas on all DTI maps. Fractional anisotropy, mean diffusivity, and axial diffusivity showed significantly inverse correlations with CC histologic grades and were significantly different between metastatic and nonmetastatic lymph nodes.